Recyclable and Degradable Poly(vinyl alcohol)/Betaine-Based Deep Eutectic Polymer Dry Gel Plastics with a High Mechanical Strength - Hanyu Zhao; Ying Jia; Ling Cai; Xiaochun Wang; Minghui He; Guangxue Chen (Gels)
Most existing polymer plastics are nonreusable and also exhibit poor biocompatibility and a poor mechanical strength–tensile strain balance. Herein, using deep eutectic polymers, we prepare reusable hydrophilic supramolecular dry gel plastics with balanced stress–strain characteristics through the hydrogen bonding of poly(vinyl alcohol) (PVA) with betaine (Bta). As PVA exhibits crystalline stiffness and abundant hydrogen-bonding sites, it is employed as a network backbone in the proposed deep eutectic supramolecular polymers. In the prepared PVA/Bta dry gel plastics, PVA and Bta are dynamically and physically crosslinked through high-density hydrogen bonding, resulting in a yield strength of ~109 MPa and toughness of up to ~210.92 MJ m−3. In addition, these plastics can be recycled at least five times in an aqueous environment while maintaining a mechanical strength of 100 MPa. Furthermore, the proposed polymers exhibit high transparency (92%) in the visible spectrum. We expect these polymers to be used in synthesizing biodegradable dry gel plastics, as well as to lead to the development of recyclable deep eutectic PVA/Bta polymers with remarkable strength.